If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 14 = 3 + 7x + -7 Reorder the terms: 14 + 4x = 3 + 7x + -7 Reorder the terms: 14 + 4x = 3 + -7 + 7x Combine like terms: 3 + -7 = -4 14 + 4x = -4 + 7x Solving 14 + 4x = -4 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 14 + 4x + -7x = -4 + 7x + -7x Combine like terms: 4x + -7x = -3x 14 + -3x = -4 + 7x + -7x Combine like terms: 7x + -7x = 0 14 + -3x = -4 + 0 14 + -3x = -4 Add '-14' to each side of the equation. 14 + -14 + -3x = -4 + -14 Combine like terms: 14 + -14 = 0 0 + -3x = -4 + -14 -3x = -4 + -14 Combine like terms: -4 + -14 = -18 -3x = -18 Divide each side by '-3'. x = 6 Simplifying x = 6
| 1+4(-4+2x)=-15+8x | | -8n+2=3+7n+10 | | 5x-120=13 | | 20+9h=92 | | -3x^2+11x+35=7-4x^2 | | -3p+8=6-(10p+3) | | 11=2+2v+7 | | -15=6x+3(4-3x) | | (x+y)(5x^2-2xy+6y^2)= | | -5(1-2x)=-55 | | -6w+(-8)w=0 | | 5(5x+2x)=9(x-3) | | 3x+16=4x+9 | | log(x)=.68 | | 2.68+2.04=-1.02d+6.1 | | -6(v+4)+2v+6=6v+6 | | 4x-11=8x+5 | | 3x-4x+3=32 | | 1.5x+1.5=3 | | 3x+16=91 | | 5x-9-3x=3x-6 | | 4.9x^2+1.85x+55.3=0 | | 10x^2+14x=-x^2+3x+5 | | 30+.5x=21+.65x | | x-7=3(x+5) | | 4x+3=-4+2x+11 | | 2x-8-2x=-1+x | | 2(4y+3)=6 | | 9x-95=38+2x | | 2x+67=6x+7 | | .40x+.60y=24 | | 3yd=12y |